STUDY OF CLINICAL PROFILE OF PSEUDO-EXFOLIATION SYNDROME AND PSEUDO-EXFOLIATION CATARACT IN A TERTIARY HEALTH CARE HOSPITAL IN WESTERN ODISHA - PANIGRAHI, SARITA; MISHRA, TAPAS R.; MISHRA, PRAGNYA P. (International Journal of Current Pharmaceutical Research, 2024)
Objective: The pseudo-exfoliation (PEX) syndrome is a complex disorder characterized by the deposition of fibrillary materials around the blood vessels of organs. This study was conducted with the aim of knowing the actual prevalence of PEX in Western Odisha and the characteristics of cataracts in those PEX patients. Methods: This cross-sectional study included 340 OPD patients and was conducted between January 1, 2021, and December 31, 2022, at Hitech Medical College and Hospital. The prevalence of PEX and cataracts was studied. The data was analyzed using basic descriptive statistics and reported in frequencies and percentages. Results: The study showed 74 patients out of 340 were diagnosed with pseudoexfoliation syndrome, with a prevalence of 23%. 42 patients (58%) were male and 32 (42%) were female, with a M: F ratio of 1.3:1. The mean age of presentation was 67 y (range 51–84 y), and the majority of patients (41%) were in the age group of 61–70 y. The increased intraocular pressure was noticed in 11 cases (15%) in our study. Two patients each had open-angle glaucoma and lens-induced glaucoma. Nuclear cataract was the most common type of cataract observed in 27% of the study group, followed by cortical cataract with nuclear sclerosis in 19% of cases. Conclusion: It is concluded that pseudo-exfoliation syndrome is more common in males than in females, with a higher number of patients in the age group of 81 y and older. Therefore, it can be assumed that it is associated with the age factor. Nuclear cataract was the most common type of cataract observed in our study population.